1973
DOI: 10.1177/002248717302400103
|View full text |Cite
|
Sign up to set email alerts
|

Specifying Teacher Competencies

Abstract: Specification of teacher competencies is a most crucial aspect of designing a competency-based teacher education program. The purpose of this article is to examine several issues related to specifying teacher competencies, specifically, the bases from which competencies might be specified, the kinds of competencies which might be specified, the persons who might be involved in specifying competencies, and the processes which might be used in specifying competencies. The &dquo;Why&dquo; of Specifying Teacher Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1973
1973
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Descriptions provided by Baker (1974); Aragon (1973);and Cooper, Jones, and Weber (1973) are illustrative of how these competencies were described in the early scholarship on teacher preparation for multicultural education. Baker referred to them as a series of sequential "stages" of training including acquisition, development, and involvement.…”
Section: Substantive Content For Infusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptions provided by Baker (1974); Aragon (1973);and Cooper, Jones, and Weber (1973) are illustrative of how these competencies were described in the early scholarship on teacher preparation for multicultural education. Baker referred to them as a series of sequential "stages" of training including acquisition, development, and involvement.…”
Section: Substantive Content For Infusionmentioning
confidence: 99%
“…These are content, commitment, competence, and confidence. Cooper et al (1973) identified four sources or frames of reference from which multicultural education competencies and content derive. Philosophical sources generate ideas about the values of humankind, the purposes of education, and the nature of learning within the contexts of cultural and ethnic pluralism.…”
Section: Substantive Content For Infusionmentioning
confidence: 99%
“…The teacher as a facilitator of student learning, serving to help students meet society's demands, was the focus of the 1973 generic competencies list that might be called the Stu- (Cooper, Jones & Weber, 1973). This model emphasizes the performance competencies of teachers and the consequent competencies specified for students, with interaction between teachers and students as the measure of teacher effectiveness.…”
Section: University Of Kentuckymentioning
confidence: 99%
“…(15,19,9,41) PBTE ist eine Weiterentwicklung von zwei schon seit Jahren bestehenden Tendenzen in der amerikanischen Lehrerausbildung, nämlich der Lernzielorientierung und der Individualisierung. (15,19,9,41) PBTE ist eine Weiterentwicklung von zwei schon seit Jahren bestehenden Tendenzen in der amerikanischen Lehrerausbildung, nämlich der Lernzielorientierung und der Individualisierung.…”
Section: "Performance-based (Competency-based) Teacher Education" (Pbte)unclassified